KOGNISI PELAKU INDUSTRI PARIWISATA DI YOGYAKARTA MENGENAI MAKNA KATA PROFESIONAL (KAJIAN SEMANTIK PROTOTYPE) - Devita Widyaningtyas Yogyanti; Annisaa Nurul Atiqah (Journal of Tourism and Economic, 2019)
In the working wold, the word “professional” related with some features of meaning which create the meaning of the word totally. To avoid different cognition among people in seeing the case of “professional”, therefore it is important to make the standard measurement as the guideliness. The different perception about what people said about “professional” can appear as a problem in the working world when there is a dissagreement cognition among the staffs. Therefore this research aimed to find the features of meaning which form the meaning of “professional”, which is the features of meaning that can be the main guideliness for a worker in doing job. The method used are qualitative and quantitative. Quantitative method used for counting and processing the result answer from the participant, who are the staffs of tourism industry, in the form of number. Qualitative method later will be used to elaborate the result in the form of sentences related to the concept of the word “professional”. Based on the analyzed data, it is found that the features which form the meaning of the word “professional” from the point of view of tourism industry workers in Yogyakarta are ability, discipline, and altruism manner. In this case, altruism manner become the most important feature in finding the level of one’s professionalism.Keyword: Professional, Cognition, Feature of meaning, Tourism, Hospitality